PENINGKATAN KESADARAN DAN KETERAMPILAN PENCEGAHAN BULLYING MELALUI WORKSHOP METODE ROLE PLAYING DAN MODEL EXPERIENTAL LEARNING - Amri Amal; Ifa Aulia; Muh. Dzul Ikram; Annisa Rifkah Fadila Abbas; Wandi Eka Nugraha (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Bullying is one of the serious problems that often occurs in schools and has a negative impact on the psychological, social, and academic development of students. This community service activity aims to increase the awareness and skills of students at SD 69 Galesong 1 in preventing bullying through the implementation of the role-playing method and experiential learning model. The implementation method used a participatory action research approach involving 26 students as the subjects. The activity was carried out in two cycles, starting with material socialization, role-playing activities, reflection, and evaluation through pre-test and post-test. The results showed a significant improvement in students’ understanding and skills. In Cycle 1, the average student score was only 46.35 with a classical mastery level of 23%. After the intervention in Cycle 2, the average score increased to 83.27 with a classical mastery level reaching 100%. In addition, students showed increased empathy, courage to reject bullying, and social skills in dealing with conflict. These findings prove that the role-playing method combined with experiential learning is effective in building anti-bullying awareness and skills, as well as creating a safer, more comfortable, and positive school environment.